An artificial reef at the edge of the deep: An interdisciplinary case study. (1st September 2021) - Ramos, Jorge; Tuaty-Guerra, Miriam; Almeida, Mariana; Raposo, Ana C.; Gaudêncio, Maria J.; Silva, Alexandra D.; Rodrigues, Nuno; Leandro, Sérgio M.; Caetano, Miguel
Abstract: Just nearby the largest submarine canyon in Europe – off the western coast of Portugal – is located the Nazaré artificial reef (NAR) deployed in 2010 and the first of its kind in this coast. NAR aimed to improve social and economic resilience of the local communities, mainly by creating a safer and closer area for fishing and to enhance commercially exploitable marine resources. The innovative part of this research lies on the fact that for the first time was developed a multidisciplinary approach for NAR. Scientific evidence from fieldwork shows that in 2015 the reef was already mature and colonized by abundant and diversified macrobenthic assemblages. No evidence of negative impacts of NAR on the soft bottom macrofauna was observed, as assemblage composition in the NAR area and in the vicinity areas is similar. In relation to the primary producers that support the subsequent food chain, there also seems to be a balance between NAR and the surrounding area since phytoplankton was equally abundant throughout the area. Experimental fisheries and underwater visual census results on ichthyofaunal communities in the reef revealed high abundance and low levels of species richness, pouting, Trisopterus luscus Linnaeus, 1758 being the most common fish species found. Concerning NAR socio-economic impact, results from direct site observations (DSOs) showed that only some small-scale fishing vessels were eligible to operate on the NAR area. Thus, comparatively to non-AR areas nearby reef use by fishing vessels differs according to spatial and temporal strata. In what perception was concerned, the NAR has contributed to fish aggregation, though being populated mostly by small fish. Fishers have stated that some factors seemed to have changed after reef deployment. Notwithstanding, the NAR may have been a valuable contribution to an apparently overall socio-economic positive impact on the local fishing community that can be corroborated by the presence of good biological indicators. Graphical abstract: Image 1 Highlights: The Nazaré artificial reef was deployed close to one of the largest submarine canyons in Europe. Phytoplankton was abundant in the artificial reef area. There was no evidence of negative impacts on soft bottom macrofauna. Trisopterus luscus (pouting) was the most common fish species found in the Nazaré artificial reef. Fishers have perceived some changes due to artificial reef deployment, mostly were positive.